Translation Strategies Applied by the Fifth-Semester Students of English Education Study Program in Translating English Written Texts into Indonesian Langauge - Afaf Astria Sapta; Azwandi Azwandi; Arasuli Arasuli (Universitas Bengkulu, 2020)
This research attempted to find out translation strategies applied by the fifth-semester students of English Education Study Program in translating English written texts into Indonesian. It was conducted by applying descriptive qualitative and quantitative approach. The subject of the research were 61 pieces of translation task collected from the lecturer into taught translation subject. Data of this research were collected from the students’ assignment about Explanation text given by the lecturer. . The data analysis was done by using translation techniques theory proposed by Suryawinata and Hariyanto (2003). The results of this research revealed that the use of each translation strategy varied in terms of frequency. The translation strategies used by the students from the most dominant to the least dominant respectively were as follows ; 1) Borrowing (56.61%); 2) Omission (29.41%); 3) Synonym (6.80%), 4) Addition (3.49%), 5) and Transposition (3.49%). The applications of reduction and expansion were not found. Among all the five translation strategies found in the students’ translation works, omission, synonym and borrowing were accurately applied. Furthermore, addition and transposition were not accurately and successfully applied by the students.